2018
DOI: 10.1158/0008-5472.can-17-3370
|View full text |Cite
|
Sign up to set email alerts
|

The EGFR T790M Mutation Is Acquired through AICDA-Mediated Deamination of 5-Methylcytosine following TKI Treatment in Lung Cancer

Abstract: Almost all patients with EGFR-driven lung cancer who are treated with EGFR tyrosine kinase inhibitors (TKI) develop resistance to treatment. A single base (c.2369C>T) transition mutation, EGFR T790M, is the most frequent resistance event after first-generation exposure to EGFR TKI. Whether T790M mutation is acquired or is selected from a pre-existing clone has been a matter of significant debate. In this study, we show that treatment with EGFR TKI leads to activation of the NFᴋB pathway, which in turn induces … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
23
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 28 publications
(24 citation statements)
references
References 40 publications
(38 reference statements)
0
23
1
Order By: Relevance
“…According to El Kadi and coworkers, the formation of EGFR T790M mutation is initiated by AICDA-mediated deamination of the 5-methylcytosine following therapy with either of the EGFR TKI. Nevertheless they observed differential gene expression of AICDA under different treatment conditions (type and dose of EGFR TKI) [25]. Therefore, a different frequency of T790M acquisition under reversible and irreversible EGFR TKI is conceivable.…”
Section: Discussionmentioning
confidence: 97%
“…According to El Kadi and coworkers, the formation of EGFR T790M mutation is initiated by AICDA-mediated deamination of the 5-methylcytosine following therapy with either of the EGFR TKI. Nevertheless they observed differential gene expression of AICDA under different treatment conditions (type and dose of EGFR TKI) [25]. Therefore, a different frequency of T790M acquisition under reversible and irreversible EGFR TKI is conceivable.…”
Section: Discussionmentioning
confidence: 97%
“…The mechanism of acquisition T790M is still unclear. El Kadi et al reported that deamination of the 5-methylcytosine to thymidine at position c.2369 generates the T790M change that alters TKI-binding affinity and causes resistance ( 24 ). In addition, the BELIEF trial showed that T790M at disease progression can be derived from the selection of preexisting EGFR T790M-positive clones or emerge de novo in initially negative cells ( 25 ).…”
Section: Discussionmentioning
confidence: 99%
“…Early diagnosis and innovations in the treatment of lung cancer have contributed towards improving the survival rate of patients. Currently, patients with EGFR-mutant NSCLC are administered a standard treatment regimen of EGFR-TKIs as they demonstrate better response rates and PFS as compared to chemotherapy 24,25. Unfortunately, almost all EGFR-mutant NSCLC patients who received first-generation EGFR-TKI therapy developed secondary drug resistance with a mean PFS range of 9.2–13.1 months 25.…”
Section: Discussionmentioning
confidence: 99%